Calcaneal fracture : standardized protocol of treatment - Daraboš, Nikica (Array, 2009)
Abstract: Calcaneal fracture (CF) treatment results are not always satisfied. Our aim was to compare medium-term results between standardized and unstandardized protocol in treatment of displaced intra-articular CF. We evaluate experience of our Department where 50 patients with CF in last 5 years – Group X have been treated with standardized protocol, and compare their postoperative results with unstandardized treatment’s effects in 50 patients with CF cured 5 years before – Group Y. As based on Sanders classification, radiographic evaluation and Maryland Foot Score, postoperative results were satisfying in 100% X and 90% Y patients with intra-articular type I, in 86% X and 70 % Y patients with type II, and sufficient in 75% X and 52 % Y patients with type III, in 50% X and 33% Y patients with type IV. We suggest standardized protocol with operative treatment for types II, III and even for type IV of intra-articular CF